A Morpho-Syntactic Analysis of Personal Names in Oǹdó - Sunday Olayinka Awolaoye (Yoruba Studies Review)
Names are important in the Yorùbá culture. It is like a lens that clearly reflects the people’s social background and their cultural ideologies. Names are means by which a person is identified. It is considered among Yorùbá to be of life longer, even than the bearer of the names, hence the need for a name to be protected from being destroyed. All these are what scholars have said about names in the standard dialect of Yorùbá. This essay explains the form and structure of personal names in the Oǹdó dialect. By this we mean an attempt is made to explain the morpho-syntactic analysis of personal names in Oǹdó.  Oǹdó dialect spoken in communities such as Ile̩-Oluji, Oǹdó, Ìdànrè, Ajùé, Òdìgbó, Òkè-Igbó, etc. The data collected were from the native speakers through interviews on the personal names. The analyses reflect that Oǹdó's personal names are morphologically derived through the de-sententialisation process. In terms of syntactic structure, most of the names are generated from simple basic sentences, compound sentences and negative sentence.